Pembelajaran Bahasa Inggris Melalui Contextual Teaching And Learning Di Kelurahan Talise Valangguni Kecamatan Mantikulore Kota Palu: Learning English through Contextual Teaching and Learning in Talise for Elementary School Students - Mappewali, A; Omolu, Fikriani Aminun; Manangkari, Ismail; Prasetyaningsih, Rahayu; Kusdiharjo, Vincentius Stephandi; Irvan, Moh. (Sambulu Gana : Jurnal Pengabdian Masyarakat, 2023)
For the people of Palu, English has yet to become an important part of communication that must be introduced to children early. English is only known and mastered by academics. Meanwhile, the general public (non-academics) uses Indonesian or regional languages in various daily communication activities. This community service activity aims to introduce English to elementary school-age children. The implementation took place in the Talise-Valangguni sub-district, Mantikulore District. The servants in this activity are lecturers and students from the Faculty of Teacher Training and Education, Muhammadiyah University, Palu. From this activity, 16 elementary school students were interested in participating in learning English. The small number of participants shows that interest and motivation in learning English still needs to be higher.